Analisis Komunikasi Antar Penggemar “Seventeen” sebagai “Cyberfandom’’ di Twitter - Eza Okta Afifah; Triarona Kusuma (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2019)
Research on “The Analysis of Communication Among Fans of Seventeen as a Cyberfandom on Twitter” comes from the observation of the fan phenomenon of a K-Pop group Seventeen on Twitter. Seventeen fans, known as Carat, use Twitter as a medium to communicate and share information between fans. The theory that used in this article are CMC theory, new media theory and cyber community theory. This article used a method of netnography or online ethnography conducted with interviews and online observation of the activitiy of Seventeen fans Twitter account. The analysis technique used in this article is qualitative analysis technique by using data reduction, data presentation and data conclusion. The results of this paper indicates that Seventeen fans exchange information and communicate with each other using Twitter. Carat uses the tweets, reply, quote tweet, retweet and direct message to communicate and exchange information on Twitter.